Does Wim Hof Method Improve Breathing Economy during Exercise? - Marko, David; Bahenský, Petr; Bunc, Václav; Grosicki, Gregory J; Vondrasek, Joseph D (Journal of clinical medicine, 2022)
(1) Background: Breathing economy during endurance sports plays a major role in performance. Poor breathing economy is mainly characterized by excessive breathing frequency (BF) and low tidal volume (VT) due to shallow breathing. The purpose of this study was to evaluate whether a 4 week intervention based on the Wim Hof breathing method (WHBM) would improve breathing economy during exercise in adolescent runners. (2) Methods: 19 adolescent (16.6 ± 1.53 years) middle- and long-distance runners (11 boys and 8 girls) participated in the study. Participants were randomly divided into experimental (n = 11) and control groups (n = 8). The study was set in the transition period between competitive race seasons and both groups had a similar training program in terms of running volume and intensity over the course of the study. The experimental group performed breathing exercises every day (~20 min/day) for 4 weeks. The control group did not perform any kind of breathing exercise. The breathing exercises consisted of three sets of controlled hyperventilation and consecutive maximum breath holds. Before and after the intervention, participants performed incremental cycle ergometer testing sessions consisting of two minute stages at 1, 2, 3, and 4 W·kg−1 with breath-by-breath metabolic analysis. During the testing sessions, BF, VT, and minute ventilation (VE) were assessed and compared. (3) Results: There were no statistically significant differences (p > 0.05) in BF, VT, or VE between experimental and control groups before or after the intervention. A nonsignificant small-to-large effect for an increase in VE and BF in both groups following the 4 week intervention period was observed, possibly due to a reduction in training volume and intensity owing to the down period between competitive seasons. (4) Conclusions: The 4 week intervention of WHBM did not appear to alter parameters of breathing economy during a maximal graded exercise test in adolescent runners.
Keywords: runners; diaphragm; adolescents; Wim Hof method; breathing